Spiritualitas dan Kewirausahaan: Eksplorasi Peran Praktik Tasawuf dalam Kesuksesan Usaha - Priyanto, Aris; Mahdafi, M. Reza; Saputri, Mita Mahda (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
This article explores the impact of Tasawuf (Islamic mysticism) practices on entrepreneurial success, focusing specifically on jeans entrepreneurs in Wonopringgo, Pekalongan District. This study adopts a qualitative approach with a Tasawuf Akhlaki framework to understand how spiritual values influence business behaviors. The subjects of the research include three entrepreneurs, with data collected through observation, in-depth interviews, and documentation. Descriptive analysis reveals that the continuity of worship practices, particularly prayer, significantly contributes to developing entrepreneurs who are resilient and have integrity. The findings affirm that entrepreneurs who are consistent in their worship practices tend to experience better business stability and growth. This study confirms that integrating Tasawuf in entrepreneurship not only enriches the personal dimensions of entrepreneurs but also yields a competitive advantage. These conclusions suggest the importance of considering spiritual factors in modern business development strategies.Abstrak: engan fokus khusus pada pengusaha celana jeans di Wonopringgo, Kabupaten Pekalongan. Penelitian ini menggunakan pendekatan kualitatif dengan kerangka tasawuf akhlaki untuk memahami bagaimana nilai-nilai spiritual mempengaruhi perilaku bisnis. Subjek penelitian meliputi tiga pengusaha, dengan data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi. Analisis deskriptif menunjukkan bahwa keberlanjutan praktik ibadah, khususnya shalat, secara signifikan berkontribusi pada pembentukan karakter pengusaha yang resilien dan berintegritas. Hasil ini menegaskan bahwa pengusaha yang konsisten dalam praktik ibadahnya cenderung mengalami stabilitas dan pertumbuhan bisnis yang lebih baik. Studi ini mengkonfirmasi bahwa integrasi tasawuf dalam kewirausahaan tidak hanya memperkaya dimensi pribadi pengusaha tetapi juga menghasilkan keuntungan kompetitif. Kesimpulan ini menyarankan pentingnya mempertimbangkan faktor spiritual dalam strategi pengembangan bisnis modern.